Code-Mixing of Indonesian Language into Geser-Gorom Language in the Comment Section of the Newpilar Seram Bagian Timur Facebook Group - Sidi, Saida; Rumalean, Iwan; Lelapary, Happy (JENDELA PENGETAHUAN, 2022)
The types, methods, and approaches used in this research are qualitative-descriptive-postpositivism. Aims to describe Indonesian Code Mixing into "Geser-Gorom" Code on the NewPilar SBT Facebook Social Meds Group. The data obtained are not numbers but words and sentences containing the Mixing of Indonesian Codes into the "Geser-Gorom" Code in the NewPilar SBT Facebook Medsos Group. The data source for this research is the NewPilar SBT Facebook Social Media Group. Data collection uses note-taking, reading, and documentation techniques. This research instrument is crucial because the researcher is present as a collector, analyzer, and description of the research results. Check the validity of the data using triangulation of data and sources. The results showed that of the three types of code-mixing, the researcher found one kind of code-mixing spoken by members of the NewPilar SBT Facebook Social Media Group, namely inward mixing. Inward code-mixing is mixing Indonesian code into the "Geser-Gorom" code, as in the speech sa iwa mu, kao loka baba. "That one is okay; you are great.